Divine hiddenness - Weidner, Veronika 1982- (Cambridge elements, 2021)
This Element provides an introduction to the hiddenness argument, as presented by John Schellenberg, and its up-to-date discussion in a comprehensible way. It concludes with a brief assessment of where things stand, from the author's point of view, and why divine hiddenness should not reduce a reflective theist's confidence in theism